MELESTARIKAN KEARIFAN LOKAL DAERAH MANGGARAI MELALUI KEGIATAN MENDONGENG PADA ANAK SEKAMI USIA SD DI PAROKI SANTU NIKOLAUS KELURAHAN GOLO DUKALMELESTARIKAN KEARIFAN LOKAL DAERAH MANGGARAI MELALUI KEGIATAN MENDONGENG PADA ANAK SEKAMI USIA SD DI PAROKI SA - Fransiska Jaiman Madu; Mariana Jediut; Maria Rahayu Anwar (PGSD UNIKA SANTU PAULUS RUTENG, 2020)
MELESTARIKAN KEARIFAN LOKAL DAERAH MANGGARAI MELALUI KEGIATAN MENDONGENG PADA ANAK SEKAMI USIA SD DI PAROKI SANTU NIKOLAUS KELURAHAN GOLO DUKAL Abstract: Storytelling is a form of oral tradition as a means of communication and recording the events of life or human civilization of the past. Fairy tales are one of the places to preserve local wisdom. As for the fairy tale here is the fairy tale of the Manggarai area. Manggarai fairy tales were chosen with the aim of introducing various local wisdoms contained in these tales. this activity aims to; 1) introducing various local wisdoms in the Manggarai area to children of primary school age; 2) growing love for various local wisdoms in the Manggarai area; 3) grow and develop children's mental and ability to speak in frontother friends.in its implementation, this activity goes through several stages namely; 1) preparation stage which includes coordination of the service team, contacting partners, determining the schedule of activities, and procuring Manggarai folklore books; 2) the stage of implementation of activities which includes mentoring and training fordevelop the ability of children SEKAMI in knowing tales and storytelling.this activity aims to improve the ability of children SEKAMI in knowing more stories and good ways of storytelling; 3) the final stage includes storytelling and evaluation activities related to the effectiveness of service activities. this activity went well and the objectives of the activity were achieved.